Hierarchical Mobility Management for VoIP Traffic - MISRA, Archan (Institutional Knowledge at Singapore Management University, 2001)
A hierarchical IP-based mobility management mechanism is proposed for VoIP applications. The suggested mechanism uses the DMA (dynamic mobility agent) architecture, based on IDMP (intra-domain mobility management protocol), for managing intra-domain mobility and the dynamic binding mechanism of SIP (session initiation protocol) for managing global mobility. This combination of network and application layer mobility management reduces the global signaling load, provides fast handoff for ongoing conversations, enables efficient global transport and supports IP-layer paging.